DEVELOPMENT OF ENTERPRISE RESOURCE PLANNING APPLICATIONS TO HELP RESOURCES MANAGEMENT OF FURNITURE COMPANY USING TECHNOLOGY WINDOWS COMMUNICATION FOUNDATION - Didiek S Wiyono; Bayu Pratama Rudy N (J@ti Undip: Jurnal Teknik Industri, 2013)
Furniture companies need the latest information of its resources to maintain efficiency and productivity. ERP can be used as a tool to manage the existing resources on furniture company and can quickly display the suitable information.The study was conducted to design a simple ERP application that can help resource management on the furniture company. ERP application built with object-oriented methods. The implementation is using web technology as the user interface, Windows Communication Foundation (WCF) as the application interface with other systems, and HTTP / HTTPS as the transport protocol to access the application.The results of study is a simple ERP application which consist of order management, production, inventory, purchasing, and reporting. ERP applications can be accessible to users through the web. For the purposes of integration, has built 72 services of WCF that can be accessed by other applications even though using different platforms.Keywords: erp, web, windows communication foundation, integration